PENGARUH MOTIVASI BERPRESTASI DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU DIMODERASI OLEH SUPERVISI AKADEMIK (Studi Kasus Pada SMP Negeri Di Kecamatan Comal Kabupaten Pemalang) - Ani Surjati, 1352020062; Suhari, Yohanes (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study examines Influence Achievement Motivation and professional competence of the teacher performance Moderated by Academic Supervision (Case Study at Junior High School in the District Pemalang Comal). This research is a census means the entire population were subjected to experiments. The population in this study were teachers Comal Junior High School in the District Pemalang totaling 135 people. In this study, using primary data obtained by questionnaire. Data analysis method used was linear regression to test the moderating effects.The results showed that the achievement motivation and significant have a positive impact on teacher performance. Professional competence has a positive and significant impact on teacher performance. Academic supervision does not affect the performance of teachers. Academic supervision does not moderate the influence of achievement motivation on teacher performance. Academic supervision does not moderate influence on the performance of the professional competence of teachers.Keywords: Supervision of Academic, Achievement Motivation, Professional Competence, Performance of Teachers